RETRACTED: Oncological Effects and Prognostic Value of AMAP1 in Gastric Cancer - Li, Jiao; Tian, Shan; Guo, Yingyun; Dong, Weiguo (Frontiers in Genetics, 2021)
Purpose: We examined the diagnostic significance, prognostic value, and potential function of AMAP1 in gastric cancer (GC). Methods: Comprehensive bioinformatic analysis was conducted to investigate differential expression of AMAP1 mRNA and protein in GC. Meta-analyses were ultilized to determine the overall prognostic correlation of AMAP1 mRNA in patients with GC. A panel of vitro assays was applied to assess target microRNA and AMAP1 protein in GC cell lines and tissues, respectively. Results: AMAP1 mRNA and protein levels were upregulated in GC specimens, compared to matched normal tissues. AMAP1 mRNA exhibited promising results regarding differential diagnosis of GC and normal tissue. Meta-analysis based on the TCGA and GEO databases revealed that high AMAP1 mRNA abundance was associated with poor overall survival (HR = 1.42; 95% CI: 1.06–1.89) and was correlated with reduced progression-free survival (HR = 1.89; 95% CI: 1.51–2.36) in GC patients. Moreover, AMAP1 was negatively correlated with miR-192-3p (r = -0.3843; P < 0.0001). A dual-luciferase assay revealed that miR-192-3p targeted AMAP1. Levels of miR-192-3p were significantly higher in GC tissues and GC cells than in normal tissues and cells. Moreover, AMAP1 silencing resulted in reduced GC proliferation, migration, and invasion. Conclusion: AMAP1 is a novel oncogene in GC and is negatively correlated with by miR-192-3p. AMAP1 may act as a diagnostic and prognostic marker of GC.